Differences of Lateral Cephalometry Values between Australo-Melanesian and Deutero-Malay Races - Cristiany Cristiany; Arlia E. Budiyanti; Adi Hidayat; Hamilah D. Koesoemahardja (Faculty of Dentistry, Universitas Indonesia, 2013)
<!--[if gte mso 9]> 72 1024x768 <![endif]--> <p class="MsoNormal" style="text-align: justify; mso-pagination: none; tab-stops: 28.0pt 56.0pt 84.0pt 112.0pt 140.0pt 168.0pt 196.0pt 224.0pt 252.0pt 280.0pt 308.0pt 336.0pt; mso-layout-grid-align: none; text-autospace: none;">Cephalometric is extensively used to study the facial morphology that supports orthodontic diagnosis and treatment planning. Correct cephalometric analyses need reference values obtained from the same ethnic, gender and age population of orthodontic patients. Objective: To compare the difference of lateral cephalometric values between Australo-Melanesian and Deutero-Malay race in 16 to 20 years of age subjects with normal occlusion. Methods: An observational with cross-sectional design study on 200 subjects (100 males and 100 females) from Australo-Melanesian and Deutero-Malay race was performed. Lateral cephalometric radiographs were taken, traced and analyzed. Results: Mann Whitney U test showed significant differences on SNA angle with median 84° for Australo-Melanesian race and 83° for Deutero-Malay race. Lower lip distance to aesthetic line 3mm for Australo-Melanesian race and 1mm for Deutero-Malay race also showed significant difference. Independent t-test showed significant differences in FM angle with mean 27.45±4.49° for Australo-Melanesian race and 28.14±5.36° for Deutero-Malay race, and upper I to APg angle 36.28±4.72°for Australo-Melanesian race and 32.69±6.24° for Deutero-Malay race. Conclusion: The Australo-Melanesian race had more protruded maxilla to cranial base, more flat mandibular plane, more proclined upper incisors, and more frontal lower lip to aesthetic line compared to Deutero-Malay race. <p class="MsoNormal" style="text-align: justify; mso-pagination: none; tab-stops: 28.0pt 56.0pt 84.0pt 112.0pt 140.0pt 168.0pt 196.0pt 224.0pt 252.0pt 280.0pt 308.0pt 336.0pt; mso-layout-grid-align: none; text-autospace: none;">DOI: 10.14693/jdi.v20i1.127